Development of a simplified model and nomogram in preoperative diagnosis of pediatric chronic cholangitis with pancreaticobiliary maljunction using clinical variables and MRI radiomics - Yang Yang; Xin-xian Zhang; Lian Zhao; Jian Wang; Wan-liang Guo (Insights into Imaging, 2023)
Key points Conventional imaging modalities were not powerful enough to diagnose chronic cholangitis. The radiomics signature based on T2-weighted MR images performed well in diagnosing chronic cholangitis. Associating the radiomics signature with clinical factors improved the diagnosis performance of chronic cholangitis.